THE EFFECT OF IMPROVEMENT ON WORK FACILITY OF COCO BRISTLE PROCESS TO OCCUPATIONAL HEALTH AND SAFETY - Huda, Listiani Nurul; Nasution, Indra (Talenta Publisher, 2018)
One of improvements on health and safety can be carried out by the improvement on work facilities used by workers during the production process. This research was conducted in one of manufacture of coco bristel which the machines are not designed ergonomically. Work posture of the worker are in standing position during the processing of coco bristle and the body position is bending that can causes fatigue at the back and spine. On the other hand, the coco bristle machine is not ergonomically designed to maintain security as workers shrink the outer shell of coir. Pulling velocity of coconut husk by spinning pliers may result in hand drawn towards the nail. Therefore, this research is needed to carried out in order to re-design the coco bristel machine so that workers can work more healthily and safely. The method used in this research is work posture asessment by Rapid Entire Body Assessment (REBA) and anthropometric concept to re-design coco bristle machine. The results show that the actual machine design gives a REBA score of 6 indicating that mprovement of work posture is in need of improvement. The improvement is carried out by redesign of the machine through consideration to the most dominant body dimension influenced the work of making coco bristel. These dimensions are the height of the elbows at standing position, hand reach, and hand grip. This improved machine design resulted in a smaller REBA score by two points than before which means that the spinal position tends to be in a more healthier position than before. As for the safety of using the machine, hand protection is added based on the dimension of hand grip. The results of this study indicate that there is a strong relationship between the machine design and size dimensions of the worker's body with the level of security and health in the work.